2014
DOI: 10.1093/jisesa/ieu030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogenetic Analysis of the Eukaryotic Translation Initiation Factor 4A Gene in Antheraea pernyi (Lipdoptera: Saturniidae)

Abstract: Eukaryotic initiation factor 4A (eIF-4A) is an essential component for protein translation in eukaryotes. The eIF-4A gene ( ApeIF-4A ) was isolated and characterized from Antheraea pernyi (Guérin-Méneville) (Lepidoptera: Saturniidae). The obtained cDNA sequence was 1,435-bp long with an open reading frame of 1,266 bp encoding 421 amino acids. The predicted amino acid sequence shared several conserved features as found in known eIF-4As and revealed 74 and 78% identities with eIF-4As of Homo sapiens L. and Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The gene-specific primer pairs for mVg , Vg [ 20 ], and KK-42BP ( KK-42-binding protein ; [ 21 ]) are listed in Table 1 . The eIF-4A gene was used as an internal control [ 22 ]. We used the reverse transcription-polymerase chain reaction (RT-PCR) method to detect the expression pattern.…”
Section: Methodsmentioning
confidence: 99%
“…The gene-specific primer pairs for mVg , Vg [ 20 ], and KK-42BP ( KK-42-binding protein ; [ 21 ]) are listed in Table 1 . The eIF-4A gene was used as an internal control [ 22 ]. We used the reverse transcription-polymerase chain reaction (RT-PCR) method to detect the expression pattern.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that A. pernyi eIF‐4A shares 82–99 % sequence identity with eIF‐5As in closely related species, and 72–73 % sequence identity with eIF‐5As in vertebrates. Sequence identity of >60 % indicates high conservation during the evolution of eukaryote organisms following divergence from a common ancestor (Embley & Martin ; Chen et al ). Furthermore, sequence alignment and prediction of functional domains revealed that the amino acid sequences of the conserved features of ApeIF‐5A, including the N‐terminal and C‐terminal domain, were even more highly conserved (Kapp & Lorsch ).…”
Section: Resultsmentioning
confidence: 99%